Leadership of Teacher in the Digital Age Affecting the Effectiveness of Academic Administration Under Prachuap Khiri Khan Primary Educational Service Area Office 2 - Jampa, Kamonthip; Lenanant, Apichat; Jirasatjanukul, Kanokrat (Education journal Faculty of Education, Nakhon Sawan Rajabhat University, 2025)
This research aimed to study 1) examine the level of digital-age leadership among teachers, 2) investigate the effectiveness of academic administration, and 3) explore the impact of teachers’ digital-age leadership on the effectiveness of academic administration in schools. This quantitative research involved 362 school administrators and teachers under the Prachuap Khiri Khan Primary Educational Service Area Office 2, selected through simple random sampling in each school. Data were collected using a questionnaire and analyzed using percentages, frequency, descriptive statistics, standard deviation, Pearson’s correlation coefficient, and stepwise multiple regression analysis. The research results were found as follows; 1) The overall level of teachers’ digital-age leadership was high, with the highest mean scores in modeling effective teaching practices, leading change, and participating in school development. 2) The overall level of academic administration effectiveness was also high, with the highest mean scores in developing educational media, innovations, and technology, improving the internal quality assurance system, and curriculum and curriculum management. 3) Teachers’ digital-age leadership, which significantly influenced the effectiveness of academic administration, was driven by self- and team development, leading change, and digital knowledge.